Wear-resistant non-stick coating, application and cooking utensil
By forming a molten layer of NiAl-Cr3C2 composite material on the surface of the aluminum alloy substrate of the non-stick pan and forming a non-stick layer of specific components thereon, the existing non-stick pan coating has poor wear resistance and insufficient impact resistance at high temperatures, and higher wear resistance and cold and hot impact resistance are achieved.
Patent Information
- Application Number
- CN202411899971.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
The coatings of existing non-stick pans have poor wear resistance and insufficient impact resistance at high temperatures, and are especially prone to damage when used alternately with cold and heat.
A melting process is used to form a moltening layer of NiAl-Cr3C2 composite material on the surface of the aluminum alloy substrate, and a non-stick layer composed of tetraethoxysilane, nanosilica sol, silane coupling agent, acetic acid and silicon carbide whiskers is formed thereon, improving the wear resistance and cold and cold impact resistance of the coating.
It significantly improves the wear resistance and impact resistance of the non-stick pan, can maintain good non-stick properties in high temperature environments, and resists the impact caused by the alternation of cold and heat, extending the service life of the coating.
Smart Images

Figure BDA0005202887290000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a wear-resistant non-stick coating, an application thereof and a cooking utensil. Background Art
[0002] Non-stick cookware is widely used due to its advantages of non-stick cooking, less smoke, easy cleaning, etc. The reason why non-stick cookware does not stick to food is mainly due to the non-stick coating inside the cookware.
[0003] At present, there are two main types of non-stick coating materials for non-stick pans on the market. The first is Teflon (PTFE, polytetrafluoroethylene) coating, which is popular for its excellent non-stick performance. However, Teflon coating can only provide good non-stick effect at relatively low temperatures, and may decompose and release harmful gases at high temperatures. The second is ceramic coating, which is generally considered a safer and more environmentally friendly option because it usually does not contain potentially harmful chemicals such as PFOA (perfluorooctanoic acid) or PTFE. In addition, ceramic coatings can withstand higher temperatures, but ceramic coatings may not be as durable as Teflon, and may wear out over time, resulting in a decrease in non-stick performance. In addition, the impact resistance is insufficient and it is easily damaged by external force impact, especially resistance to cold and hot shocks. Therefore, the wear resistance and impact resistance of ceramic coatings need to be further improved. Summary of the invention
[0004] A first aspect of the present invention provides a wear-resistant non-stick coating, in order to solve the problems of poor wear resistance and insufficient impact resistance of the non-stick coating in the prior art.
[0005] The first aspect of the present invention adopts the following technical solution:
[0006] A wear-resistant non-stick coating, comprising a sprayed layer formed on the surface of a substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer; wherein:
[0007] The composition of the sprayed layer is NiAl-Cr 3 C 2 Composite materials;
[0008] The non-stick layer comprises the following parts:
[0009] Film-forming components include tetraethoxysilane, nano-silica sol, and silane coupling agent;
[0010] a catalytic component including acetic acid;
[0011] Strengthening components include silicon carbide whiskers.
[0012] In the above scheme, before forming the non-stick layer, the sprayed layer is formed on the surface of the substrate by the spraying process, which can assist the non-stick layer on the surface and improve the wear resistance of the non-stick pan.
[0013] The composition of the sprayed layer was further screened, and the composition of the sprayed layer was selected as NiAl-Cr 3 C 2 Composite material, NiAl-Cr 3 C 2 In the composite material, NiAl is the body of the sprayed layer, providing adhesion and improving the corrosion resistance of the base aluminum alloy. 3 C 2 As a hard dispersed phase, it is evenly distributed in the NiAl layer, which can greatly improve the wear resistance and scratch resistance of the inner surface of the pot under high temperature conditions. 3 C 2 The composite material can form a closer connection with the aluminum alloy substrate, further improving the wear resistance.
[0014] In NiAl-Cr 3 C 2 On the basis of the sprayed layer, the film-forming components are further selected and optimized. Tetraethoxysilane, silica sol and silane coupling agent are used as film-forming substances. After coating, a dense coating can be quickly formed, and the processing performance of the coating is also improved.
[0015] In the above-mentioned film-forming component system, using acetic acid as a catalyst to promote the film-forming reaction can further improve the density of the formed coating.
[0016] In the above system, this solution also adds silicon carbide whiskers, which can not only strengthen the film structure, but also improve the thermal conductivity of the ceramic coating, making the temperature in the pot more uniform.
[0017] During the use of cooking utensils, the pots need to be washed after cooking in order to cook the next dish. At this time, the high-temperature pots that have just finished cooking are subjected to a sudden cold shock when rinsed with cold water. Repeated alternation of hot and cold will cause damage to the coating.
[0018] The inventors also unexpectedly discovered that the silicon carbide whiskers added in this solution can significantly improve the film layer's resistance to thermal shock.
[0019] Preferably, per 100 parts, the NiAl and Cr 3 C 2 The mass ratio is (94-96):(4-6).
[0020] Further preferably, per 100 parts, the NiAl and Cr 3C 2 The mass ratio is 95:5.
[0021] Preferably, the wear-resistant coating composition comprises 15-30% tetraethoxysilane, 13-27% nano silica sol, 5-10% silane coupling agent, 0.2-1% acetic acid, 0.5-2% silicon carbide whisker, and 25-64.3% deionized water. The above percentages are all weight percentages.
[0022] In the above scheme, the ratio of each component is further optimized. Under this ratio, each component plays its own function, and promotes each other, giving the coating high wear resistance and resistance to cold and hot shocks.
[0023] Preferably, the content of the nano silica sol does not exceed the content of the tetraethoxysilane. In the film-forming system of tetraethoxysilane, silica sol and silane coupling agent in the present invention, it is found that if the content of the nano silica sol exceeds the content of the tetraethoxysilane, the film formation is unstable and the wear resistance of the coating is significantly reduced.
[0024] The further optimized ratio is as follows:
[0025] 20-25% tetraethoxysilane, 15-20% nano silica sol, 5-8% silane coupling agent, 0.2-1% acetic acid, 1-1.5% silicon carbide whisker, 25-64.3% deionized water. The above percentages are all weight percentages. Under this ratio, the coating formed by the wear-resistant coating composition has its density significantly improved.
[0026] The further optimized ratio is as follows:
[0027] 22-25% tetraethoxysilane, 18-20% nano silica sol, 5-8% silane coupling agent, 0.2-1% acetic acid, 1-1.5% silicon carbide whisker, 25-64.3% deionized water. The above percentages are all weight percentages.
[0028] The further optimized ratio is as follows:
[0029] Tetraethoxysilane 25%, nano silica sol 18%, silane coupling agent 5%, acetic acid 1%, silicon carbide whisker 1%, deionized water 50%, and the above percentages are all weight percentages.
[0030] Preferably, the thickness of the sprayed layer is 50 μm to 200 μm, for example, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 110 μm, 120 μm, etc.
[0031] More preferably, the thickness of the sprayed layer is 80 μm to 120 μm.
[0032] Preferably, the roughness Ra of the sprayed layer is 2 μm to 7 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, or 7 μm.
[0033] More preferably, the roughness Ra of the sprayed layer is 3 μm to 5 μm.
[0034] Preferably, a wire drawing surface is formed on the surface of the substrate, and the sprayed layer is formed on the wire drawing surface.
[0035] Preferably, the drawing depth of the drawing surface is 20 μm to 30 μm.
[0036] Preferably, the substrate is an aluminum alloy, and a sand layer is formed on the surface of the substrate before the spraying layer is formed.
[0037] Preferably, the roughness of the surface of the sand layer is 3 μm to 10 μm.
[0038] Preferably, the thickness of the non-stick layer is 20 μm to 40 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc.
[0039] A second aspect of the present invention provides the use of the above-mentioned wear-resistant non-stick coating for cooking utensils, such as non-stick pans.
[0040] A third aspect of the present invention provides a cooking utensil comprising the above-mentioned wear-resistant non-stick coating.
[0041] By implementing the above technical solution, the present invention has the following beneficial effects:
[0042] 1. The present invention provides a spraying layer on the surface of the aluminum alloy substrate of the non-stick pan by a spraying process, and the spraying layer is made of NiAl-Cr 3 C 2 Composite material, NiAl is the body of the sprayed layer, which provides adhesion and can also improve the corrosion resistance of the base aluminum alloy. 3 C 2 As a hard dispersed phase, it is evenly distributed in NiAl, which can greatly improve the wear and scratch resistance of the pot surface under high temperature environment.
[0043] 2. The present invention also provides NiAl-Cr 3 C 2The optimization of the specific composition ratio of the composite material not only further improves the wear resistance, but also significantly improves the gravity impact resistance. The sprayed layer can also enhance the mechanical strength of the substrate itself, making it more durable.
[0044] 3. The present invention sets NiAl-Cr 3 C 2 On the basis of the sprayed layer, the composition of the non-stick layer formed on the surface of the sprayed layer is further optimized. The film-forming system of tetraethoxysilane and nano-silica sol is used. Not only can a dense coating be formed quickly after coating, but it can also be compatible with NiAl-Cr 3 C 2 Better connections are formed between the sprayed layers and the processing properties of the coating are improved.
[0045] 4. In the film-forming system of tetraethoxysilane and nano-silica sol, acetic acid is used as a catalyst to promote the film-forming reaction, which can further improve the density of the formed coating.
[0046] 5. Adding silicon carbide whiskers to the film-forming system of tetraethoxysilane and nano-silica sol can not only strengthen the film structure, but also improve the thermal conductivity of the ceramic coating, making the temperature in the pot more uniform. It also significantly improves the coating's resistance to cold and hot shocks, allowing it to withstand repeated cold and hot shocks caused by repeated cooking and cleaning. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the specific embodiments of the present invention will be clearly and completely described below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] The present embodiment provides a wear-resistant non-stick coating, including a sprayed layer formed on the surface of an aluminum alloy substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the sprayed layer is composed of NiAl-Cr 3 C 2 Composite materials, and NiAl and Cr 3 C 2 The mass ratio is 96:4.
[0050] The non-stick layer contains the following components in weight percentage: 20% tetraethoxysilane, 15% nano silica sol, 5% silane coupling agent, 0.5% acetic acid, 1% silicon carbide whisker, 3% copper chrome black, and 55.5% deionized water.
[0051] The above-mentioned wear-resistant non-stick coating is formed by a method comprising the following steps:
[0052] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0053] S2. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0054] S3. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0055] S4. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0056] Example 2
[0057] The present embodiment provides a wear-resistant non-stick coating, including a sprayed layer formed on the surface of an aluminum alloy substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the sprayed layer is composed of NiAl-Cr 3 C 2 Composite materials, and NiAl and Cr 3 C 2 The mass ratio is 95:5.
[0058] The non-stick layer specifically comprises: 26% tetraethoxysilane, 20% nano silica sol, 8% silane coupling agent, 0.5% acetic acid, 0.5% silicon carbide whisker, 3% copper chrome black, and 42% deionized water.
[0059] The above coating is formed by a method comprising the following steps:
[0060] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0061] S2. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0062] S3. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0063] S4. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0064] Example 3
[0065] The present embodiment provides a wear-resistant non-stick coating, including a sprayed layer formed on the surface of an aluminum alloy substrate by a spraying process and a non-stick layer formed on the surface of the sprayed layer, wherein the sprayed layer is composed of NiAl-Cr 3 C 2 Composite materials, and NiAl and Cr 3 C 2 The mass ratio is 94:5.
[0066] The non-stick layer contains the following components in weight percentage: 18% tetraethoxysilane, 13% nano silica sol, 8% silane coupling agent, 0.6% acetic acid, 1.5% silicon carbide whisker, 4% copper chrome black, and 54.9% deionized water.
[0067] The above coating is formed by a method comprising the following steps:
[0068] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0069] S2. Thermal spraying to form a spray layer: plasma spraying spray layer composite powder, flame velocity 800m / s, particle velocity 500m / s, forming a spray layer, the thickness is 55μm, the surface roughness Ra is 5μm;
[0070] S3. Post-processing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0071] S4. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0072] Example 4
[0073] The present embodiment provides a wear-resistant non-stick coating, which is different from the embodiment 1 in that the non-stick layer contains the following components in weight percentage: 30% tetraethoxysilane, 20% nano-silica sol, 10% silane coupling agent, 1% acetic acid, 1.5% silicon carbide whisker, 4% copper chrome black, and 33.5% deionized water.
[0074] Example 5
[0075] This embodiment provides a wear-resistant non-stick coating, which is different from Embodiment 1 in that the non-stick layer contains the following components in weight percentage: 25% tetraethoxysilane, 18% nano-silica sol, 5% silane coupling agent, 1% acetic acid, 1% silicon carbide whisker, and 50% deionized water.
[0076] Example 6
[0077] The present embodiment provides a wear-resistant non-stick coating, which is different from the embodiment 1 in that the non-stick layer contains the following components in weight percentage: 15% tetraethoxysilane, 25% nano-silica sol, 10% silane coupling agent, 0.2% acetic acid, 0.4% silicon carbide whisker, 4% copper chrome black, and 52.9% deionized water.
[0078] Example 7
[0079] This embodiment provides a wear-resistant non-stick coating, which is different from Example 1 in that the non-stick layer contains the following components in weight percentage: 18% tetraethoxysilane, 27% nano-silica sol, 6% silane coupling agent, 0.5% acetic acid, 1.5% silicon carbide whiskers, 4% copper chrome black, and 43% deionized water.
[0080] Example 8
[0081] The present embodiment provides a wear-resistant non-stick coating, which is different from the embodiment 1 in that the non-stick layer contains the following components in weight percentage: 20% tetraethoxysilane, 15% nano-silica sol, 5% silane coupling agent, 0.5% acetic acid, 1% silicon carbide whisker, 5% boron carbide, 3% copper chrome black, and 50.5% deionized water.
[0082] Example 9
[0083] The present embodiment provides a wear-resistant non-stick coating, which is different from the embodiment 1 in that the non-stick layer contains the following components in weight percentage: 20% tetraethoxysilane, 15% nano-silica sol, 5% silane coupling agent, 0.5% acetic acid, 1% silicon carbide whisker, 8% boron carbide, 3% copper chrome black, and 50.5% deionized water.
[0084] Comparative Example 1
[0085] The difference from Example 1 is that no thermal spraying layer is provided.
[0086] The above coating is formed by a method comprising the following steps:
[0087] S1. Pre-treatment: The inner tank workpiece is subjected to wire drawing to form a wire drawing surface with a wire drawing depth of 22 μm, and then subjected to stamping, riveting, ultrasonic cleaning, and degreasing;
[0088] S2. Polishing: polish with 40-80 mesh sandpaper, clean, and dry at 80℃;
[0089] S3. Spraying to form a non-stick layer: Electrostatic spraying of ceramic coating, 80℃ / 10min surface drying, 280℃ / 20min curing, thickness of 30μm, completed.
[0090] Example 10
[0091] This embodiment provides a non-stick pan, the substrate is an aluminum alloy, and the wear-resistant non-stick coatings of embodiments 1-9 and comparative example 1 are formed on the substrate. The thickness of the sprayed layer is 50 μm, and the thickness of the non-stick layer is 35 μm.
[0092] The coatings on each cookware were subjected to relevant performance tests, including heat resistance, wear resistance, and resistance to gravity impact under hot and cold shocks. The test methods and test results are as follows.
[0093] Detection method:
[0094] Gravity impact resistance under hot and cold shock: Place the sample in a constant temperature oven at 300℃±5℃ for 30 minutes, then immediately place the sample in room temperature water for cooling (the water temperature is 20℃±2℃, and the sample should be completely immersed in water), repeat three times, and then conduct gravity impact performance test.
[0095] Wear test: Use a 3M 7447C industrial scouring pad with water to wipe the coating of the specimen with a force of 10N. One round trip is counted as one time. If abrasion marks with a width of more than 1mm on the exposed substrate appear on the surface or 10 linear abrasion marks with a length of more than 2mm expose the substrate, the test is stopped.
[0096] The test results are shown in Table 1.
[0097] Table 1 Test results of relevant properties of coatings corresponding to the coatings of various embodiments and comparative examples
[0098]
Claims
1. A wear-resistant non-stick coating, characterized in that: It includes a spray layer formed on the surface of the substrate by a spray process and a non-stick layer formed on the surface of the spray layer; wherein, The composition of the thermal spraying layer is NiAl-Cr3C2 composite material; The non-stick layer comprises the following parts: Film-forming components include tetraethoxysilane, nano-silica sol, and silane coupling agent; a catalytic component including acetic acid; Strengthening components include silicon carbide whiskers.
2. A wear-resistant non-stick coating according to claim 1, characterized in that: The mass ratio of NiAl to Cr3C2 is (94-96):(4-6) per 100 parts.
3. The wear-resistant non-stick coating according to claim 1, characterized in that: The components are mixed according to the following weight percentages: 15-30% of tetraethoxysilane, 13-27% of nano-silicon dioxide sol, 5-10% of silane coupling agent, 0.2-1% of acetic acid, 0.5-2% of silicon carbide whisker, and 25-64.3% of deionized water.
4. A wear-resistant non-stick coating according to claim 1 or 2, characterized in that: The content of the nano-silica sol does not exceed the content of the tetraethoxysilane.
5. The wear-resistant non-stick coating according to claim 3, characterized in that: The components are mixed according to the following weight percentages: 22-25% tetraethoxysilane, 18-20% nano-silica sol, 5-8% silane coupling agent, 0.2-1% acetic acid, 1-1.5% silicon carbide whisker, and 25-64.3% deionized water.
6. The wear-resistant non-stick coating according to claim 3, characterized in that: The components are mixed according to the following weight percentages: 25% tetraethoxysilane, 18% nano-silica sol, 5% silane coupling agent, 1% acetic acid, 1% silicon carbide whisker, and 50% deionized water.
7. The wear-resistant non-stick coating according to claim 1, characterized in that: The thickness of the sprayed layer is 80 μm to 120 μm.
8. The wear-resistant non-stick coating according to claim 1, characterized in that: The roughness Ra of the sprayed layer is 2 μm to 7 μm.
9. The wear-resistant non-stick coating according to claim 1, characterized in that: The non-stick coating has a thickness of 20 μm to 40 μm.
10. The wear-resistant non-stick coating according to claim 1, characterized in that: A wire drawing surface is formed on the surface of the substrate, and the spraying layer is formed on the wire drawing surface.
11. The wear-resistant non-stick coating according to claim 6, characterized in that: The drawing depth of the drawing surface is 30 μm to 100 μm.
12. The wear-resistant non-stick coating according to claim 1, characterized in that: The substrate is an aluminum alloy, and a sand layer is formed on the surface of the substrate (101) before the spraying layer is formed.
13. Use of the wear-resistant non-stick coating according to any one of claims 1 to 12, characterized in that: For cooking utensils.
14. A cooking utensil, characterized in that: The invention comprises the wear-resistant non-stick coating as claimed in any one of claims 1 to 12.
Citation Information
Patent Citations
Method for preparing high-temperature wear-resistant coating on continuous casting crystallizer copper alloy plate surface
CN102851632A
High-hardness fluoride-free high-temperature-resistant water-based paint
CN103819950A
Preparation and application method of water-based ceramic anticorrosive paint
CN104193288A
Chromium carbide and carbon titanium nitride particle dispersion consolidated aluminium oxide base ceramic composite material and its preparation method
CN1911856A
Wear-resistant non-stick coating structure for cooker surface
CN216137612U
Cited By
Ceramic non-stick coating for kitchen and preparation method thereof
CN121736536A